(untitled) (Bombay Hospital Journal, 2024)
As compared to other cranial nerves, hypoglossal nerve palsy is rare; and is often associated with other lower cranial nerve palsies. The most common causes of hypoglossal nerve palsies are tumors followed by trauma, stroke, surgery, infection, and multiple sclerosis. We report a case of a 55-year-old male presenting with dysphagia, dysarthria, and difficult mastication. He was diagnosed to have isolated hypoglossal nerve palsy secondary to compression by internal carotid artery dissection (ICAD). He was treated conservatively with antiplatelets and showed improvement on a 6-month follow-up. ICAD is a dangerous entity with possible endangering complications and hence recognition of it is critical for appropriate treatment and prevention of possible complications. ICAD should be considered in differential diagnosis for isolated hypoglossal nerve palsy.